The Seismogenic Zone: AYOUNG KIM. - LAI, OPHELIA (ArtAsiaPacific)
The article offers information on the works of Seoul-based artist Ayoung Kim, and the way she is tackling the disruptions of COVID-19 pandemic. It mentions that the artist collaborated with composer Heera Kim to devise a scrambled choral performance using a custom algorithm, dissolving the artist's research-based libretto about this history into barely discernible phrases and non-lexical vocalizations.